GRUPO OPERATIVO DE SUPORTE ÀS FUNÇÕES PARENTAIS: RELATO DA DINÂMICA GRUPAL - Dreher, Daniela Z.; Campos, Iris F. A.; Gomes, Joseila S.; Rios, Karina R.; Tessari, Ana M. B.; Gross, Carolina; Hoffmann, Ananda; Steinke, Gabriela V.; Baú, Fernanda (Salão do Conhecimento, 2013)
Resumo